A BEM-based algorithm for soft-in soft-output detection of co-channel signals - Gallo, A.S.; Vitetta, G.M.; Chiavaccini, E. (IEEE transactions on wireless communications, 2004)
In this paper, a soft-in soft-out multiuser detector for synchronous co-channel signals transmitted over frequency-flat Rayleigh-fading channels is described. The derivation of the proposed algorithm is based on a generalization of the expectation-maximization (EM) algorithm, called Bayesian EM. Performance results for both uncoded and coded phase shift keying transmissions show the efficacy of the proposed multiuser detection technique over slowly time-varying fading channels in a two-user system.